PENGARUH HARGA, KUALITAS PELAYANAN DAN KELENGKAPAN PRODUK TERHADAP KEPUASAN KONSUMEN LIBERTY MART WATULIMO TRENGGALEK - Laura Dhea Dora (Sekolah Tinggi Pariwisata Mataram, 2022)
Consumers are factors that play an important role for the sustainability of a business. Without consumers, the business cannot operate properly. Therefore, customer satisfaction is one of the things that need to be considered by business owners. This study aims to examine the effect of partially and simultaneously the variables of price, service quality and product completeness on consumer satisfaction. The research method applied is quantitative and sampling using accidental sampling technique. The number of samples in this study were 100 respondents, who accidentally met and matched the criteria determined by the researcher. The analytical tools used in this research are validity and reliability tests, classical assumption test, multiple linear regression analysis, partial test (t test), simultaneous test (f test) and determinant coefficients. Based on the results of the t test, it is stated that partially the price and product completeness variables have no significant effect on consumer satisfaction. Meanwhile, the service quality variable partially has a significant effect on customer satisfaction. Based on the results of the F test, it can be concluded that simultaneously the variables of price, service quality and product completeness have an influence on consumer satisfaction. Consumer satisfaction can be explained by the price, quality service and completeness of the product by 23,6%. While the remaining 76,4% can be explained by factors outside the study